A study of some antioxidants and biochemical variables in the sera of breast cancer patients from southern Iraq after receiving chemotherapy and radiotherapy (Journal of the College of Basic Education, 2022)
In order to investigate the case of a change in antioxidants and some of biochemical changes in the serum of breast cancer patients by receiving chemotherapy and radiation therapy, it have been measure the level of anti-oxidants and the level of blood fat in the serum. The study included 60 female suffering from breast cancer They were treated at AL-Shifa Oncology Centre and Hospital, radiation and nuclear medicine in Misan province (treatment chemical therapy group(1) = 30 and a radiation therapy group(2) = 30) in addition to the 29 female from collage of medicine-Misan healthy represent the control group, for the period from October 2015 until February 2016. The level of MDA , was significant increase in the chemotherapy group (P ≤ 0.05) and it was significantly decreased in the radiotherapy group (P ≤0.001) compared with the control group. And the level of vitamin A, was significant increase in two groups of chemotherapy (P ≤ 0.05) and radiotherapy group (P ≤ 0.05) compared with the control group. The level of vitamin C, was significant increase in a chemotherapy (P ≤ 0.05) and radiotherapy group (P ≤ 0.05) compared with the control group. The level of cholesterol was significant increase in the chemotherapy group (P ≤ 0.05) and radiotherapy group (P ≤ 0.05) compared with the control group. And the level of triglycerides was significant decrease in the chemotherapy group (P ≤ 0.05) and radiotherapy group (P ≤ 0.05) compared with the control group.